Case report: High-grade endometrial stromal sarcoma with adrenal glands metastases: An unreported site of metastasis - Zhang, Tao; Feng, Run-lin; Yin, Si-fan; Feng, Wen-bo; Yin, Zhi-yuan; Wang, Hao; Ke, Chang-Xing (Frontiers in Oncology, 2022)
Background Endometrial stromal sarcoma is a relatively rare malignant tumor that derives from the malignant transformation of primitive uterine mesenchymal cells. It can lead to distant metastases. High-grade endometrial stromal sarcoma is extremely rare. The adrenal glands are an unreported site of metastasis. Case summary A 71-year-old woman with a diagnosis of endometrial stromal sarcoma 30 months ago. After receiving treatment with radiotherapy and chemotherapy, the patient was kept asymptomatic during the follow-up until 2 years later, when she complained of dyspnea. Pulmonary and right adrenal gland metastases were detected by 18F-FDG PET/CT. The right upper lobe mass was diagnosed as a high-grade endometrial stromal sarcoma metastasis after postoperative pathology. Due to the patient’s high risk of surgery, as she had many underlying diseases, we performed adequate preoperative preparation. The physical examination revealed that a hard mass was palpable in the right renal area. The right adrenal mass was resected in our hospital. Immunohistochemistry showed ER (-), PR (-), CD10 (+), P16 (+), Ki-67 (50%). The final diagnosis on pathological examination was a high-grade ESS metastatic to the right adrenal gland. The patient continued treatment in other hospitals after surgical resection. After four months of postoperative follow-up, metastasis was detected again during a PET/CT examination at an outside hospital. Conclusion Endometrial stromal sarcoma is rare, and the adrenal glands are an unreported site of metastasis. It has no specific clinical symptoms and mainly found for other reasons. The diagnosis still depends on pathology and immunohistochemistry. If there is no relevant past history, it is difficult to exclude a primary adrenal tumor.